A new monoclonal antibody against rhamnogalacturonan II and its application to immunocytochemical detection of rhamnogalacturonan II in Arabidopsis roots. Issue 10 (3rd October 2018) - Zhou, Ye; Kobayashi, Masaru; Awano, Tatsuya; Matoh, Toru; Takabe, Keiji
ABSTRACT: Rhamnogalacturonan II (RG-II) is a region of pectin macromolecules that is present in plant primary cell walls. RG-II can be solubilized from cell walls as a borate-RG-II complex (B-RG-II), where two RG-II fragments are cross-linked via a borate diester linkage. Here, a rabbit monoclonal antibody against B-RG-II was prepared, which recognized both B-RG-II and RG-II monomers without borate ester-crosslinking. A pectic fragment with unknown structure was also recognized by the antibody, but neither homogalacturonan nor rhamnogalacturonan I was recognized. Immunoelectron microscopic analyses of Arabidopsis root tip cells were performed using this antibody. The signal was detected in developing cell plates and cell walls, which were denser in longitudinal walls than in transverse walls. These results coincide with our previous results obtained in suspension cultured tobacco cells, confirming that RG-II is present in cell plates at an early stage of their assembly. Abbreviations: B: boron; B-RG-II: borate-RG-II complex; ELISA: enzyme-linked immunosorbent assay; IgG: immunoglobulin G; mBSA: methylated bovine serum albumin; PGA: polygalacturonic acid; PLL: poly-l -lysine; RG-I: rhamnogalacturonan I; RG-II: rhamnogalacturonan II Graphical abstract: : Immunogold labeling of rhamnogalacturonan II in Arabidopsis root cells using rabbit monoclonal antibody. Signals were detected in both cell walls (A) and cell plates (B).